Identification of Genetic Loci and Candidate Genes Related to Grain Zinc and Iron Concentration Using a Zinc-Enriched Wheat ‘Zinc-Shakti’ - Rathan, Nagenahalli Dharmegowda; Sehgal, Deepmala; Thiyagarajan, Karthikeyan; Singh, Ravi; Singh, Anju-Mahendru; Govindan, Velu (Frontiers in Genetics, 2021)
The development of nutritionally enhanced wheat (Triticum aestivum L.) with higher levels of grain iron (Fe) and zinc (Zn) offers a sustainable solution to micronutrient deficiency among resource poor wheat consumers. One hundred and ninety recombinant inbred lines (RILs) from 'Kachu'× 'Zinc-Shakti' cross were phenotyped for grain Fe and Zn concentrations and phenological and agronomically important traits at Ciudad Obregon, Mexico in the 2017-18, 2018-19 and 2019-20 growing seasons and Diversity Arrays Technology (DArT) molecular marker data were used to determine genomic regions controlling grain micronutrients and agronomic traits. We identified seven new pleiotropic QTL for grain Zn and Fe on chromosomes 1B, 1D, 2B, 6A and 7D. The stable pleiotropic QTL identified have expanded the diversity of QTL that could be utilized in breeding for wheat biofortification. Nine RILs with the best combination of QTL for Zn and Fe have been identified to be used in future crossing programmes and to be screened in elite yield trials before releasing as biofortified varieties. In silico analysis revealed several promising candidate genes underlying QTL, including those belonging to the families of the transporters and kinases known to transport small peptides and minerals (thus assisting mineral uptake) and catalyzing phosphorylation processes, respectively.